A Pesquisa em ensino de biologia no programa de pós-graduação em ensino de ciências da Universidade Federal Rural de Pernambuco : características e contribuições no período de 2003 a 2009 - SILVA, Michelle Garcia da (2011)
The study assumes substantially the characteristic of a bibliographic review, in order to analyze the contributions of the Graduate Program in Science Education, at Federal Rural University of Pernambuco (PPGEC / UFRPE) for biology teaching, using as reference the thesis developed in the program area. To achieve this purpose were selected on 41 dissertations defended in the Teaching of Biology (PPGEC / UFRPE) from 2003 until 2009.The analysis is developed based on certain descriptors of the Documentation Centre in Science Teaching (CEDOC) - Year of the defense, Author and advisors, level of education and thematic focus - and other descriptors chosen by us - Gender of academic work, Procedures of Research, teaching strategies and Biology Subarea. The results are presented in order to clarify data on the overview of the research developed in the Teaching of Biology PPGEC / UFRPE during the studied period compared with the panorama of national research in this area, that is, tracing similarities, limits and possibilities of that research with the latter. Thus, it was observed that the characteristics of research in Teaching of Biology PPGEC/ UFRPE in the examined period are in accordance with those of national research in the area, although the program displays certain characteristics that are reflections of their process of formation.